solve equation -x+3y+10z=8 4x-9y-34z=-17 3x+5y-2z=46
- print Print
- list Cite
Expert Answers
calendarEducator since 2011
write5,349 answers
starTop subjects are Math, Science, and Business
You may use elimination method, hence, if you decide to eliminate the variable x, you may multiplicate by 4 the first and you need to add the result to the second equation, such that:
`4(-x+3y+10z) = 4*8 => -4x + 12y + 40z = 32` (multiplication by 4)
`-4x + 12y + 40z + 4x - 9y - 34z= 32- 17` (addition to the second equation)
Reducing like terms yields:
`3y + 6z = 15 `
Factoring out 3 yields:
`3(y + 2z) = 15 => y + 2z = 5 => y = 5 - 2z`
You need to eliminate the variable x considering the first and the third equation, hence, you should multiplicate the first equation by 3 such that:
`3(-x+3y+10z) = 3*8 => -3x + 9y + 30z = 24`
You need to add the result to the third equation such that:
`3x + 5y - 2z - 3x + 9y + 30z= 46 + 24`
Reducing like terms yields:
`14y + 28z = 70 `
Factoring out 7 yields:
`7(2y + 4z) = 70 => 2y + 4z = 10 => y + 2z = 5`
You need to substitute `5 - 2z` for y in the given equations of system such that:
`-x+3(5-2z)+10z=8 => -x+15-6z+10z=8 => -x+4z=8-15=>-x+4z=-7`
`3x+5(5-2z)-2z=46 => 3x+25-10z-2z=46=> 3x-12z=46-25 => 3x-12z=21 => x-4z=7`
Adding the equations `x+4z=-7` and `x-4z=7` yields:
`x-4z+x+4z=7-7 => 2x = 0 => x = 0`
Substituting 0 for x in the equations of the system yields:
`{(3y+10z=8),(-9y-34z=-17),(5y-2z=46):}`
Multiplicating the first equation by 3 yields:
`9y + 30z = 24`
Add this equation to the second `-9y-34z=-17` such that:
`9y + 30z - 9y - 34z = 24 - 17`
`-4z = 7 => z = -7/4`
Substituting `-7/4` for z in equation that relates z and y yields:
`y = 5 - 2z => y = 5 + 14/4 => y = 5 + 7/2 => y = 17/2`
Hence, evaluating the solution to the system of equations yields `x=0, y=17/2, z=-7/4.`
Related Questions
- Solve the system of equations: x+5y-2z=16 3x-3y+2z=12 2x+4y+z=20
- 2 Educator Answers
- Solve the equation y=4x+3.
- 3 Educator Answers
- Solve the simultaneous equations 4x+y=-1 4x+3y=7
- 1 Educator Answer
- `27^(4x-1)=9^(3x+8)` Solve the equation.
- 1 Educator Answer
- Solve the equation x^3-3x^2-6x+8 = 0
- 1 Educator Answer
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.